2022
DOI: 10.3389/fpsyt.2022.993555
|View full text |Cite
|
Sign up to set email alerts
|

University freshmen's excessive smartphone use and psychological safety during the COVID-19 pandemic

Abstract: Although excessive smartphone use has been confirmed as being associated with specific representations of mental health (e. g., anxiety, depression, wellbeing, etc.) throughout the COVID-19 pandemic, the relationship between excessive smartphone use and cognitive representations of mental health (i.e., psychological safety) is not yet fully understood. This study aimed to identify the association between excessive smartphone use and psychological safety among university freshmen during the COVID-19 pandemic; i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 75 publications
1
2
0
Order By: Relevance
“…This study examined the influence of self-compassion on patient care practices among nurses, considering the impact of various demographic variables. The findings revealed a positive association between self-compassion and patient care practices, aligning with previous literature indicating that self-compassion training enhances nurses' resilience, reduces burnout, and enables them to provide more compassionate care (17,18). Engaging in self-compassion practices is crucial for improving nurses' well-being and their professional quality of life, ultimately benefiting patient care (19).…”
Section: Discussionsupporting
confidence: 83%
“…This study examined the influence of self-compassion on patient care practices among nurses, considering the impact of various demographic variables. The findings revealed a positive association between self-compassion and patient care practices, aligning with previous literature indicating that self-compassion training enhances nurses' resilience, reduces burnout, and enables them to provide more compassionate care (17,18). Engaging in self-compassion practices is crucial for improving nurses' well-being and their professional quality of life, ultimately benefiting patient care (19).…”
Section: Discussionsupporting
confidence: 83%
“…In order to obtain a balance of the satisfaction and happiness with the previous situation, individuals will continuously increase the amount of time using mobile phones. Therefore, individuals generally tend to delay going to bed in order to have more time to use mobile phones to satisfy themselves [31,32]. A recent longitudinal study also confirmed that front-side phone addiction significantly predicted post-test bedtime procrastination [33].…”
Section: Introductionmentioning
confidence: 96%
“…During the lockdown and social distancing measures implemented amidst the coronavirus disease 2019 (COVID-19) pandemic, the utilization of DDCI, such as smartphones, desktop computers, laptops, and tablets, increased due to the popularization of remote work, education, entertainment, and social interaction [ 15 , 16 ]. Particularly, Peru declared a state of emergency in March 2020, leading to the implementation of social distancing measures, including quarantine [ 17 ].…”
Section: Introductionmentioning
confidence: 99%